2020
DOI: 10.1177/0300060520946171
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus magnesium sulfate as an adjuvant to local anesthetics in spinal anesthesia: a meta-analysis of randomized controlled trials

Abstract: Objective To compare the efficacy of dexmedetomidine and magnesium sulfate as an adjuvant to local anesthetics in spinal anesthesia. Methods A search of PubMed, Medline, Embase, the Cochrane Library, and Google Scholar was performed. Randomized controlled trials comparing the efficacy of dexmedetomidine and magnesium sulfate as a local anesthetic adjuvant in spinal anesthesia were identified. The primary outcome was sensory block duration. The mean difference (MD) or odds ratio along with the 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The precise mechanism by which magnesium acts as an analgesic is still ambiguous, but it is suggested that NMDA receptor antagonism and calcium channel blockade are involved. 7,24,25 Numerous researchers [26][27][28] have investigated the effect of MgSO4 in various orthopaedic surgeries, but, to our knowledge, the current study is the first involving limb amputations. Among the more recent ones, 2 studies found significant reduction in pain scores and prolonged time to first analgesia request in patients undergoing arthroscopic knee surgeries under GA and epidural anaesthesia (EA), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which magnesium acts as an analgesic is still ambiguous, but it is suggested that NMDA receptor antagonism and calcium channel blockade are involved. 7,24,25 Numerous researchers [26][27][28] have investigated the effect of MgSO4 in various orthopaedic surgeries, but, to our knowledge, the current study is the first involving limb amputations. Among the more recent ones, 2 studies found significant reduction in pain scores and prolonged time to first analgesia request in patients undergoing arthroscopic knee surgeries under GA and epidural anaesthesia (EA), respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Dex has been successfully used for spinal and intravenous anesthesia in animals and humans without causing significant respiratory depression, pruritus, nausea, or vomiting. 8 , 9 In addition to epidural administration, Dex has also been administered intrathecally as an adjuvant to local anesthetics to improve the anesthetic effect, provide stable hemodynamic conditions, and prolong postoperative analgesia. 9 , 10 Furthermore, both intrathecal and intravenous injections of Dex alone or as an adjuvant were found to be effective for pain relief.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 In addition to epidural administration, Dex has also been administered intrathecally as an adjuvant to local anesthetics to improve the anesthetic effect, provide stable hemodynamic conditions, and prolong postoperative analgesia. 9 , 10 Furthermore, both intrathecal and intravenous injections of Dex alone or as an adjuvant were found to be effective for pain relief. 11 , 12 Therefore, we hypothesized that Dex also provides an analgesic effect or enhances the analgesic effect of local anesthetics.…”
Section: Introductionmentioning
confidence: 99%